Proceedings of the 19th Annual International Conference on Mobile Computing &Amp; Networking - MobiCom '13 2013
DOI: 10.1145/2500423.2500449
|View full text |Cite
|
Sign up to set email alerts
|

Interference alignment by motion

Abstract: Recent years have witnessed increasing interest in interference alignment which has been demonstrated to deliver gains for wireless networks both analytically and empirically. Typically, interference alignment is achieved by having a MIMO sender precode its transmission to align it at the receiver. In this paper, we show, for the first time, that interference alignment can be achieved via motion, and works even for single-antenna transmitters. Specifically, this alignment can be achieved purely by sliding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 27 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Fortunately, recent research using coil arrays provides positionfree solutions to the misalignment problem and it is found that charging efficiency increases from 4.8% to 64% [28]. Another option is to use mechanisms similar to "sliding antennas" [29] to fine tune and align the orientations of coils on demand.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, recent research using coil arrays provides positionfree solutions to the misalignment problem and it is found that charging efficiency increases from 4.8% to 64% [28]. Another option is to use mechanisms similar to "sliding antennas" [29] to fine tune and align the orientations of coils on demand.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike BBN, they either require APs to exchange samples over the backbone [4], work only for the downlink traffic [26], assume presence of significant number of clients [19], require multiple antennas at transmitters or receivers [11], require the antennas to be physically moved [3] to a certain point, require the channel to change from one slot to another [7], precode over exponential number of time slots [7], or provide limited throughput gain [3], or do not scale with number of APs [11]. These assumptions are not practical in mobile networks since if the client is stationary, the channel may not change [27] from one packet to another.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, we create the opportunity by mobility and quantify the diversity with microbenchmarks. The work closest to this proposal is MoMiMo [6], where the receiver adjusts its antenna in centimeter scales to actively perform interference alignment. While MoMiMo is a specific scheme optimizing for a given user, this paper is a generalization to a broader architecture.…”
Section: Related Workmentioning
confidence: 99%
“…(2) Infrastructure mobility may not be viewed as a onesize-fit-all solution, rather as a spectrum of opportunities illustrated in Figure 1. The opportunities range from centimeter scale antenna mobility to exploit multipath opportunities [6], to feet scale tethered mobility to evade wireless shadows and interferences, to full scale macromobility that minimize distance to clients. Network designers can choose to operate at different points on this spectrum, depending on user's requirements, budget, applications, and psychological comfort.…”
mentioning
confidence: 99%